AN ECONOMIC STUDY ABOUT THE DEMAND OF MAJOR RED and WHITE MEAT IN IRAQ OF 1990 – 2012 USING LINEAR APPROXIMATION MODELOF ALMOST IDEAL DEMAND SYSTEM - & Jabra, Abdul-Mageed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Despite rising the economic level of the Iraqi citizen, but there was a shortage in completing consumer's needs of animal protein. The high price of some sources of animal protein led capita turning to other alternatives to fill shortage and these turnings made destabilizations in demand of required quantities of these goods, hence on its productivity and imported quantities. This paper aimed to evaluate the functions of fish, chicken and red meat demand in Iraq due to fish considered as a good alternative of meat as it is an important source of animal protein. Demand function were evaluated according to linear approximation model of Almost Ideal Demand System (AIDS), the study showed that the special Marshal's price elasticity was the highest for chicken followed by fish and red meat. The elasticity of expenditure of red meat showed that it considered luxury goods where it was more than 1 and there was no satiate in, while the elasticity of expenditure of fish and chicken could be essential goods as it was less than 1 and that represented the reality of Iraqi citizen.